Fatwa Bahthul Masail Nahdhatul Ulama dalam Penggunaan Ubatan Penundaan Haid Di Bulan Ramadan dari Perspektif Maqāṣid Al- Sharīʿah: The Fatwa of Bahtsul Masail Nahdlatul Ulama on the Use of Menstruation-Postponing Medication during Ramadan from the Perspective of Maqāṣid al-Sharīʿah - Hakim, Abdul; Ahmad, Ridzwan; Syed Jaafar, Syed Mohd Jeffri (Jurnal Fiqh, 2025)
Fatwas of Bahthul Masail Nahdlatul Ulama (NU) play an important role in addressing contemporary issues faced by Muslims including the use of drugs to delay menstruation in Ramadan. The purpose of this investigation is to examine the fatwa of Bahthul Masail NU (Nahdhatul Ulama), especially regarding the law of using drugs to delay menstruation for Muslim women in Ramadan from the perspective of maqāṣid al-sharī’ah. This study employs the documentation method, with data analysis conductedthrough a descriptive qualitative approach, using maqāṣid al-sharī’ah as the primary measuring stick. The results of the study show that the NU Bahthul Masail agreed to permit the use of drugs to suspend menstruation in the month of Ramadan with certain conditions. Among these are that it does not harm the user, does not result in the termination of offspring (by destroying reproductive cells), and does not have an effect on future pregnancies. This fatwa also celebrates the needs of Muslims in worship in accordance with today’s scientific developments and advances which still prioritize maṣlaḥah ‘āmmah. This necessity allows Muslim women to double their reward in Ramadan in addition to achieving the privilege of Lailatul Qadr that Allah has promised in that month.